Spin Physics in Semiconductors - Dyakonov, Mikhail I. (Springer Series in Solid-State Sciences, 2008)
This book describes beautiful optical and transport phenomena related to the electron and nuclear spins in semiconductors with emphasis on a clear presentation of the physics involved. Recent results on quantum wells and quantum dots are reviewed. The book is intended for students and researchers in the fields of semiconductor physics and nanoelectronics.